The Information Quality impact on Learning Platforms - de Lima, Cláudio; Cid Bastos, Rogério; Caetano Bastos, Lia (RENOTE, 2021)
Information quality (IQ) is a multidisciplinary area that can be understood as a measure of the value that information provides to its consumer. In order to obtain it, in the learning ecosystem, it is necessary to take into account the increasingly important role of learning platforms (LP). The purpose of this article was to analyze the IQ impact on LP. For this, an integrative literature review was conducted. Analysis of this field shows that IQ has a significant impact on LP, as it increases user satisfaction, favors the use, positively influences the intention of continuity and is an essential factor for the mobile learning acceptance.